Autophagy suppresses radiation damage by activating PARP-1 and attenuating reactive oxygen species in hepatoma cells. (3rd August 2019) - Wang, Xiangdong; Tu, Wenzhi; Chen, Dong; Fu, Jiamei; Wang, Juan; Shao, Chunlin; Zhang, Jianghong
Abstract: Purpose: To investigate the relationship between autophagy and radiation damage of human hepatoma cells and to explore the role of reactive oxygen species (ROS). Materials and methods: HepG2 cells were exposed to X-rays, then the protein expressions of microtubule-associated protein 1 light chain 3 (LC3) and poly ADP-ribose polymerase-1 (PARP-1) were measured by Western blot assay, the formation of autophagosomes was detected by an autophagy detection kit, the intracellular ROS level was measured by flow cytometer, and DNA damage was evaluated by the incidence of micronuclei (MN). A CCK-8 kit was used to measure the proliferation ability of irradiated cells with or without N -acetyl-l -cysteine (NAC) treatment. In some experiments, the hepatoma cells were transferred with LC3 siRNA or PARP-1 siRNA before irradiation. Results: The protein expressions of LC3 and PARP-1 and the inductions of autophagosomes and intracellular ROS were increased in the irradiated HepG2 cells. Pretreatment of cells with NAC relieved the irradiation-induced inhibition of cell proliferation. When HepG2 cells were transfected with the LC3 siRNA, the over-expression of PARP-1 was diminished in the irradiated cells. Compared with the control group, the inhibitions of LC3 and PARP-1 increased ROS level in the irradiated HepG2 cells and hence sensitized radiation responses of both proliferation inhibition and MN induction. Conclusion: Autophagy upregulates the expression of PARP-1 and relieves radiation damage by reducing the generation of ROS.